Strategies for Guidance and Counseling to Address Quarter-Life Crisis in Students’ Career Decision-Making in Higher Education: A Systematic Literature Analysis - Noveriyanti, Grace; Masya, Hardianysah; Primanisa, Reiska (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study aims to systematically examine the guidance and counseling strategies used to address the Quarter-Life Crisis (QLC) among university students, particularly in the context of career decision-making. Using the Systematic Literature Review (SLR) method, this research analyzes 62 scientific articles published between 2020 and 2025 and retrieved from the Scopus database. The selection process followed the PRISMA 2020 flow, involving stages of identification, screening, and inclusion based on relevance and publication quality criteria. The synthesis results show that the guidance and counseling strategies applied in addressing QLC are multidimensional and encompass five main approaches: strengthening psychological aspects (self-efficacy and career adaptability), adaptive coping strategies, spiritual and reflective approaches, social support from the surrounding environment, and the use of data-based assessments in career decision-making. These findings highlight the importance of holistic and contextual approaches in designing effective and sustainable guidance and counseling services. This study also contributes to the development of guidance and counseling science by emphasizing the integration of spiritual and existential values into career counseling practices for university students. The uniqueness of this study lies in its integrative emphasis on spiritual and existential dimensions as essential foundations in the development of career counseling strategies that not only address crisis resolution but also holistically and contextually shape students’ sense of life meaning.